Komercjalizacja usług triple play w ramach sieci międzyorganizacyjnych na podstawie nowoczesnych rozwiązań billingowych - Bełz, Grzegorz; Czemarmazowicz, Aneta (Commercialization of triple play services in inter-organization networks based on modern billing solutions, 2006)
The article presents an emerging, new model of triple play services commercialization, which can be treated as a fresh example of inter-organization networks. Triple play market might be perceived as interesting research filed because of on-going convergence of well known sectors such as telecommunication, networked services and media. The authors briefly describe Multibilling as an example of technology enabler, which induces the creation of a wider inter-organization network.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1132, s. 19-27